Morphometric and anatomic characteristics of pronator quadratus muscle - Nurşen Zeybek; Özcan Gayretli; Yüsra Nur Şanlıtürk; Ayşin Kale (Chinese Journal of Traumatology)
Purpose: In surgical procedures commonly employed for the management of scaphoid and distal radial fractures, the incision and dissection of the pronator quadratus muscle play a pivotal role. Nevertheless, comprehensive investigations into the anatomical intricacies of the pronator quadratus muscle have been relatively scarce within the clinical community. In light of this, our study endeavors to make a substantive contribution to the medical literature by conducting a meticulous examination of the morphology and morphometry of this muscle. Methods: This study is a cross-sectional observational study conducted on 22 cadaveric upper extremities (44 sides) preserved between January 2005 and December 2018 at Istanbul University. The study included specimens with intact dissection areas and no prior surgical intervention. Observations focused on the morphometry of the pronator quadratus muscle and related anatomical structures. Statistical analysis was performed using SPSS v23.0, employing Student's t-test and paired t-test, with significance set at p < 0.05. Results: Significant differences were found in the morphometric measurements of the pronator quadratus muscle between the right and left upper extremities, particularly in the vertical distance between the proximal and distal attachment points of the pronator quadratus to the radius (p = 0.008). Additionally, significant differences were observed between male and female samples for radius length (p < 0.001), ulna length (p < 0.001), pronator quadratus width (p < 0.001), and the vertical distance between pronator quadratus attachment points on both the radius (p = 0.001) and ulna (p = 0.001). Furthermore, significant correlations were identified between radius length and parameters such as the vertical distance between pronator quadratus attachment points on both the radius (p = 0.002) and pronator quadratus width (p = 0.030), and between ulna length and parameters including the vertical distances on the radius (p = 0.001) and ulna (p = 0.024). Conclusion: In light of our comprehensive analysis, which encompasses not only the anatomical features of the pronator quadratus muscle but also its vascular supply and the organization of its neurovascular structures, we posit that our study holds significant implications for the field of orthopedic surgery. We anticipate that this research will furnish valuable insights that can inform and enhance orthopedic procedures.